Recurrence Rate of Cervical Cancer in Jakarta - Purwoto, Gatot; Vitantri, Fara; Purbadi, Sigit; Feharsal, Yuri; Novianti, Lisa; Scovani, Laurensia (European Journal of Oncology and Environmental Health, 2023)
Introduction: Cervical cancer is one of the ten most commonly diagnosed cancer in the world population. It is estimated there are around 570.000 new cases, with 3.3% deaths in 2018. The recurrence rate for cervical cancer ranges from 8% to 26% and usually appears within 2-3 years after the first treatment. The recurrence rate of cancer is one quality service in healthcare.; thus, the authors decide to evaluate this issue. Materials and Methods: This multicenter and retrospective study reporting 262 patients of all stage cervical cancer who met inclusion criteria from 2015 to 2019 in national reference teaching hospitals in Jakarta, Indonesia. Patients were treated with radical hysterectomy, radiation, and chemotherapy and observed for five years period. Univariate and multivariate analyses were performed to investigate the recurrence of cervical cancer. Results: The recurrence rate over all stages after primary treatment is 21.4%. The recurrence rate early stage and advanced stage is 20% and 38%, respectively. Univariate and multivariate analysis revealed parity, cancer stage, tumor size, histotype, and differentiation affecting the recurrence of the disease. Cox multivariate modeling determined the significant factors are parity (Hazard Ratio (HR) = 0.5, p-value <0.01), cancer stage (Hazard Ratio (HR) = 1.6, p-value 0.013), tumor size (Hazard Ratio (HR) = 2.08, p-value 0.018), histotype (Hazard Ratio (HR) = 2.6, p-value <0.01), and differentiation (Hazard Ratio (HR) = 0.5, p-value 0.01). Conclusion: The recurrence rate of cervical cancer is related to the cancer stage. The higher cancer stage resulted in a higher recurrence rate.